GAMBARAN FAKTOR DOMINAN PENCETUS ARTHRITIS RHEUMATOID DI WILAYAH KERJA PUSKESMAS DANGUANG DANGUANG PAYAKUMBUH TAHUN 2018 - Mariza Elsi (Menara Ilmu, 2018)
Joint pain is often referred to as arthritis is a heterogene disease caused bysupersturation of uric acid, especially in the joints so as to stimulate the process ofimflamasi. Arthritis is an unknown inflammatory disorder that usually affects thesynovial joint. The objective of the study was to analyze the dominant factor of RA causewith age variable of gender, genetic, diet, activity and comorbidities. The researchmethod used is analytical descriptive, sampling accidental sampling technique with total31 samples. The data were collected by using questionnaires.The result of the research is based on statistical test of 6 dominant factors of AR influence5 dominating AR in Danguang-danguang Publik Health. The overall conclusion foundthat the final age of the elderly were more dominantly suffering from AR, the moredominant the AR patient, the bad diet dominates the AR patient, the heavy physicalactivity dominates the AR patient and the presence of comorbidity does not dominate inAR patient.Keywords: Arthritis, picture of the originator